Architecture to connect sensor networks with Internet and services provided - SUN Ji-min1; SHEN Yu-long2; SUN Yu3; ZHANG Si-dong1 (Tongxin xuebao)
Connecting wireless sensor networks （WSN） with Internet and providing effective services to the Internet us-ers are the heated research issues. The architecture of connecting WSN with Internet was proposed,Internet-WSN gate to realize the data-package transmission between WSN and Internet was designed. The methods of providing services were presented with the thought of network middleware. The analysis and the comparison show that the architecture presented solves the problem of connecting WSN with Internet from two levels: networks and services. This architecture has the advantages of corresponding with the network protocols available,transparent for users,simultaneously connecting sev-eral WSN with Internet,low cost and conveniently offering services.